2006
DOI: 10.1213/01.ane.0000228859.95126.69
|View full text |Cite
|
Sign up to set email alerts
|

??-Adrenoreceptor Antagonists Attenuate Brain Injury After Transient Focal Ischemia in Rats

Abstract: Beta-adrenoreceptor antagonists experimentally reduce cardiac and renal injury after ischemia and are also clinically useful for myocardial infarction and severe burns. In addition, beta-adrenoreceptor antagonists provide neuroprotective effects after focal cerebral ischemia in experimental settings. We conducted the present study to compare the neuroprotective effects of several beta-adrenoreceptor antagonists in rat transient focal cerebral ischemia. Halothane-anesthetized normothermic adult male Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…In the brain, β1-adrenoceptors are expressed mainly in neurons whereas β2-adrenoceptors are largely restricted to the glial cells (Nicholas et al, 1996). In the intact brain, both non-selective and β1-adrenoceptor selective blockers have been shown to decrease infarct volume and enhance functional recovery in a transient focal ischemia model (Goyagi et al, 2006; and references cited therein). However, the cellular mechanism responsible for such apparent neuro-protection by β-adrenoceptor blockers is not known.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, β1-adrenoceptors are expressed mainly in neurons whereas β2-adrenoceptors are largely restricted to the glial cells (Nicholas et al, 1996). In the intact brain, both non-selective and β1-adrenoceptor selective blockers have been shown to decrease infarct volume and enhance functional recovery in a transient focal ischemia model (Goyagi et al, 2006; and references cited therein). However, the cellular mechanism responsible for such apparent neuro-protection by β-adrenoceptor blockers is not known.…”
Section: Introductionmentioning
confidence: 99%
“…First, because this experiment was performed in young, healthy rats, the results of this study cannot be directly applied to a general human population. Second, because blood esterase activity is higher in rats than in humans, the blood level of landiolol could be different from that in humans [15]. Third, the PaO 2 /FiO 2 ratio showed a tendency of improvement even though the differences were not significant.…”
Section: Discussionmentioning
confidence: 91%
“…The antioxidative effect of landiolol has been described in some papers [14,15]. Kimura-Kurosawa et al [5] demonstrated that landiolol exhibited a lipid peroxidation-reducing effect in isolated guinea pig hearts subjected to ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Junker et al [80] showed that clenbuterol induces neuroprotective effects via an increase in nerve growth factor expression and that this beneficial effect is blocked by propranolol. Goyagi et al [81,82] recently examined the neuroprotective effects of several beta-blockers in rats with transient focal cerebral ischemia. The rats received an intravenous infusion of saline, propranolol, carvedilol, esmolol, and landiolol 30 min before MCA occlusion, and the infusion was continued for 42 h. Cerebral infarct volumes in the cortex were lower in rats treated with propranolol (72 ± 33 mm 3 ), carvedilol (64 ± 25 mm 3 ), esmolol (65 ± 18 mm 3 ), and landiolol (44 ± 18 mm 3 ) than in saline-treated rats (205 ± 28 mm 3 ).…”
Section: Central Nervous System Effectsmentioning
confidence: 99%